Scales for Assessing Reading Motivation in Primary School Students - Agreda Sigindioy, Teresa Marinelly (2025)
The purpose of this article is to serve as a reference for the appropriate use of reading motivation scales in primary school students. The scales presented have been applied in America, Europe, and Asia. The evaluation of their theoretical strength and psychometric characteristics reflects a diverse panorama regarding their quality; the reader is invited to be critical before using them for their study. Four scales on reading motivation for primary school students are presented, these are: Y-CAIMI (Gottfried, 1990), MRQ (Wigfield y Guthrie, 1997), RSPS (Henk y Melnick, 1995) and SRQ-RM (De Naeghel et al., 2012). The qualitative method was used to review the literature on reading motivation scales in different bibliographic databases. Additionally, through hermeneutics, a critical analysis of each of the scales was carried out. It was concluded that the Y-CAIMI scale (Gottfried, 1990) presents little depth and conceptual clarity, making it unreliable for measuring intrinsic motivation for reading. On the other hand, it was identified that the MRQ scale (Wigfield y Guthrie, 1997) presents low reliability, in case of using it, the factors that compose it should be reviewed. Finally, it is recommended to use the SRQ-RM (De Naeghel et al., 2012) and RSPS (Henk y Melnick, 1995) scales, these two have high validity and reliability, consistency in theory and in items. Finally, it is recommended to use the SRQ-RM (De Naeghel et al., 2012) and RSPS (Henk & Melnick, 1995) scales, as both demonstrate high validity and reliability, with consistency in their theoretical framework and items. It is also recommended to assess the theoretical robustness and psychometric characteristics of any scale before using it. The reader is encouraged to critically evaluate the suitability of a scale before applying it to their research.